An urban project for Costanera of Asunción (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2014)
A premise “Progetto Urbano Costa di Asunción – P.U.C.A” (Urban Project of Asun-ción’s Coast) is the title of the undersigned’s (awarded the cum laude honor) master’s thesis, developed between July 2013 and June of 2014, under the supervision of Prof. Anna Irene Del Monaco from Sapienza – Università di Roma (Rome, Italy) and Prof. Ricardo Meyer from UNA – Universidad Nacional de Asunción (Asunción, Paraguay). The thesis project has been awarded the Sapienza Foundation scholarship and honor on June 20th 2013, allowing for a three month (July-October 2013) in-situ stay, during the initial phase of the investiga-tion. In Guaraní (native language of the Tupì-Guaraní populations and an official langua-ge of the Republic of Paraguay, still diffusely spoken) the word “pucà” (also spelled pukà) means “smile” (noun): such title is the summa of the spirit with which the following work was conceived. Visits – even dealing with situations of relative risk – and established rela-tions with local occupants of the project’s area gave the operative guidelines of the work: designing with social compromise, involving the recipients concretely in the construction of the project in an attempt to interpret their wills and expectations. The objective was to re-turn a project capable of generating what seemed to be, to the eyes of whom is writing, often missing in the thoughts and looks of the local inhabitants: confidence in one’s capabilities, hope in a better future, expectations that things will go better. In one word: the missing smile.